From Jugendbewegung to RAF: Youth, Friendship, and Protest in Post-Wall German Cinema - Nicole Thesz (Studies in 20th & 21st Century Literature, 2010)
Recent German-language films frame anti-establishment activities as a rejuvenating force. In Die fetten Jahre sind vorbei (2004) and Was tun, wenn’s brennt? (2001), the young filmmakers Hans Weingartner and Gregor Schnitzler take a nostalgic approach to the tradition of protest in Germany. Volker Schlöndorff, in contrast, builds on first-hand memories of the 1970s and the RAF, depicting the escalation of violence in Die Stille nach dem Schuß (2000). This paper explores the ways in which the three films foreground personal motivations, rather than political causes, arguing that friendship is used to gauge the success of protest. While the friends in Die fetten Jahre and Was tun? are (re)united through their activism, the terrorist plots portrayed in Stille lead to the protagonist’s isolation and untimely death. Ultimately, Schlöndorff places German history at the center of the tragic plotline, whereas the younger filmmakers take a position of ironic distance vis-à-vis the past. By placing a strong emphasis on community, these three films indicate that reunification and globalization give rise to dreams of friendship and protest in post-Wall Berlin.
Keywords: Die fetten Jahre sind vorbei; Was tun; wenn’s brennt?; Hans Weingartner; Gregor Schnitzler; nostalgia; nostalgie; Volker Schlöndorff; RAF; 1970; Die Stille nach dem Schuß; terrorist; terrorism; Germany; film; ironic distance; reunification; post-Wall Berlin; Berlin Wall